A study of dynamic strength index in Thai national badminton players: Case presentation - Prajongjai, V.; Songsupap, T. (Science and Racket Sports VI, 2019)
Currently, at least 27 badminton tournaments were held globally. Especially, HSBC BWF World Tour Finals, HSBC BWF World Tour Super 1000, HSBC BWF World Tour Super 750, HSBC BWF World Tour Super 500, and HSBC BWF World Tour Super 300 - each of which between 2 to 3 matches were played monthly. Therefore, sports scientists should be knowledgeable about the physical change of badminton players in response to provision of suitable training compliant with their physical fitness, their corporeal fitness will reach its highest levels in the shortest period of time due to the efficacious practice. The purpose of this study is to illustrate changes in dynamic strength index of Thai national badminton players before and after 2 competitions. Four of Thai national badminton players were recruited to be tested for dynamic strength index (DSI) by 400s force plate plus mid-thigh pull rig. Peak force during counter movement jump and Isometric mid-thigh pull were analysed by Ballistic measurement program. The finding from this study revealed that dynamic strength index of them were not significant as a between before and after (P> .05). On the other hand, the dynamic strength index of three players were increased but the other one was remain unchanged. This study suggests that training program after competition should be emphasize on strength first and then switch to power and power endurance.